The Death of the actor: Marcus Ofilius Hilarius. Plin. NH VII 184–185 - Darab, Ágnes (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The name of Marcus Ofilius Hilarius occurs in no other source besides book VII of Pliny’s encyclopaedia. With this in mind, the narrative giving an extensive account of the death of the actor needs further explanation. The present paper takes a look at the narrower and broader context of this detail, which lends the story a meaning and a structuring function within the Naturalis Historia. This inquiry enables us to draw certain conclusions not only about book VII, but the whole encyclopedia as well.